Energy-efficient optical coating for flat glass - Saidur, Rahman; Hasan, M.M.; Haseeb, A.S. Md. Abdul; Masjuki, Haji Hassan (Asian Network for Scientific Information, 2008)
In this study, the recent trends for optical coatings in glass industries have been explored for the variety of climate dependent applications. Different coated glazings have been presented with their optical and thermal characteristics. A comparative analysis among types of coated products is also performed. It has been observed that for warm climate it is necessary to block near infra red portion of sunlight to reduce solar heat gain through windows. On the other hand, for cold climate it is necessary to allow the whole portion of light and it is necessary to block the IR radiation from escaping out to keep the interior space warm. For this purpose, Ag or Ag-alloy metallic thin film meet the requirements but they reduce visible transmittance as well. So for increasing visible transmittance, a dielectric layer of high refractive index is required. Here a variety of dielectric layers are studied. Finally for reaching the goal of low energy buildings in both warm and cold climates, appropriate optical coatings for architectural flat glass have been recommended.